Legality of Forced Marriage Performers of Khalwat According to the View of Syafi'iyah Fiqh - Karimuddin, Karimuddin; Maimun, Maimun; Musana, Maulisa (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Khalwat is being alone with a man who is not a mahram. In some areas, especially in Aceh, when the perpetrators of seclusion occur, the local community provides sanctions for the perpetrators of seclusion and then the perpetrators of seclusion are married. Based on these problems, this study wants to discuss how the legality of the marriage of the perpetrators of khalwat in Syafi'iyyah Fiqh. This research is descriptive qualitative research, and in collecting data the author uses the documentation review method. The results of the study indicate that forced marriages against perpetrators of khalwat or perverts are categorized into illegitimate marriages because they are not justified by syara' the occurrence of coercion in marriage. While on the other hand, the marriage can be valid if the forced marriage fulfills the elements of coercion permitted by syara'.